Determinants of Liquidity Risk in Indonesian Islamic and Conventional Banks - Raditya Sukmana (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2016)
The purpose of the study is to examine the causes of the liquidity risk  in Islamic and conventional banks in Indonesia using panel data regression method. The study found the significant and positive relation of ROA and NPF with the liquidity risk, whereas the negative and significant relation of CAR with the liquidity risk in Indonesian Conventional Banks. Meanwhile in Islamic banks, CAR result significantly positive effect on liquidity risk, while ROA shows negative and significant result. Possible explanation for this is that, given the huge profit by the conventional banks, it has more chance to allocate it as liquidity reserve as well as increasing the facilities (improvement on technology). When the NPL is high, conventional banks will increase the liquid assets as a buffer. Unlike that of conventional banks, the Islamic banks in Indonesia might allocate capital as liquidity reserves and might allocate ROA in fixed assets or financing or technology. The result confirm that the role of capital and bank’s performance in indeed important to the banking liquidity DOI: 10.15408/aiq.v8i2.2871